Frontispiece: Photo‐responsive nanozymes: Mechanism, activity regulation, and biomedical applications (View 1/2021). Issue 1 (6th February 2021) - Wang, Chaohui; Wang, Hongyu; Xu, Bolong; Liu, Huiyu
Abstract : In article number 20200045, Huiyu Liu and her colleagues summarize and discuss the recent progress of photo‐responsive nanozymes. Nanozymes as natural enzyme mimics have gained much attention in the biomedical field but still suffer from low enzyme‐like activity limitations. This review focuses on the mechanism, activity regulation strategy, and biomedical applications of photo‐responsive nanozymes. It also summarizes the current issues and prospects of photo‐responsive nanozymes for clinical‐orientated applications. The cover image features different photo‐responsive nanozymes, while a laser beam illuminates the nanozymes, showing the interaction between light and the nanozymes. The background contains blood vessels and tumors, representing the biomedical domain of nanozymes.